Flower-like microparticles and novel superparamagnetic properties of new binary Co1/2Fe1/2(H2PO4) 2·2H2 O obtained by a rapid solid state route at ambient temperature - Boonchom, Banjong; Thongkam, Montree; Kongtaweelert, Samart; Vittayakorn, Naratip (My University, 2009)
A new binary Co1/2Fe1/2(H2PO4) 2·2H2O was synthesized by a simple, rapid and cost-effective method using CoCO3-Fe(c)-H3PO4 system at ambient temperature. Thermal treatment of the obtained Co1/2Fe1/2(H2PO4) 2·2H2O at 600 °C yielded as a binary cobalt iron cyclotetraphosphate CoFeP4O12. The FTIR and XRD results of the synthesized Co1/2Fe1/2(H2PO4) 2·2H2O and its final decomposed product CoFeP4O12 indicate the monoclinic phases with space group P21/n and C2/c, respectively. The particle morphologies of both binary metal compounds appear the flower-like microparticle shapes. Room temperature magnetization results show novel superparamagnetic behaviors of the Co1/2Fe1/2(H2PO4) 2·2H2O and its final decomposed product CoFeP4O12, having no hysteresis loops in the range of ±10,000 Oe with the specific magnetization values of 0.045 and 12.502 emu/g at 10 kOe, respectively. The dominant physical properties of the obtained binary metal compounds (Co1/2Fe1/2(H2PO4) 2·2H2O and CoFeP4O12) are compared with the single compounds (M(H2PO4)2·2H2O and M2P4O12; where M = Co, Fe), indicating the presence of Co ions in substitution position of Fe ions. © 2009 Elsevier Ltd. All rights reserved.
Keywords: A. Inorganic compounds; B. Chemical synthesis; C. Infrared spectroscopy; Ceramics; D. Magnetic properties; Thermogravimetric analysis (TGA)